Economic analysis of budget surplus in Singapore. - Ng, Li Yen. (2008)
The project is on the economic analysis of budget surplus in Singapore. Due to the fact that available literature is highly limited, an attempt was made to explore its macroeconomic implications. An empirical study was conducted to find out whether cointegration exists between budget surplus and various macroeconomic variables, based on a previous study.However, results were dismal and an explanation was given as to why it had been so.